Guilty feeling pada Seorang Wanita Lesbian yang ada di Palembang - Anissa Siti Ri’ayah; Dwi Hurriyati (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2021)
This research aims to understand the factors that cause a lesbian woman to feel guilty feeling good with their parents, God created it later in themselves. The impact after they undergo as a lesbian woman and the expression of guilty feelings towards her family. And also what are the factors that cause a lesbian woman. The researcher used a qualitative research design and used a phenomenological approach to determine the factors that cause lesbian women to feel a guilty feeling. In this study, researchers used 2 research subjects and 4 people as sources of information. The results of this study found that the cause of the subject to feel guilty feeling was due to fear of punishment that would be given by God the creator and also did not want his late father to feel disappointed with what they had done and also did not want his mother to feel the sadness that the subject had done. Then also the subject realizes that what has been done is an untrue act that has violated the established norms and rules. This is the factor that causes lesbian women to feel a guilty feeling